2003
DOI: 10.1051/0004-6361:20030261
|View full text |Cite
|
Sign up to set email alerts
|

XMM-NEWTON High resolution spectroscopy of NGC 5548

Abstract: Abstract. We analyze a 137 ks exposure X-ray spectrum of the Seyfert 1 galaxy NGC 5548 obtained with the XMM-Newton Reflection Grating Spectrometer. Due to the long exposure time, the spectrum is of higher statistical quality than the previous observations of this AGN. Therefore, we detect for the first time in NGC 5548 inner-shell transitions from O  to O  ions, and the Unresolved Transition Array of M-shell iron. The warm absorber found from this X-ray observation spans three orders of magnitude in ioni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
141
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 16 publications
16
141
1
Order By: Relevance
“…For the 40 ks RGS spectrum of NGC 3783, Blustin et al (2002) measured the abundances to be consistent with solar, with the exception of Fe. Similar abundances were measured by Steenbrugge et al (2003) for NGC 5548 using a 137 ks RGS spectrum, as well as by Blustin et al (2007) for a 160 ks RGS spectrum of NGC 7469. Holczer et al (2007) determined the abundances for IRAS 13349+2438 and NGC 3783 using the updated dielectronic recombination rates and determined abundances relative to Fe consistent with proto-solar ratios for O, Ne, Mg, Si, and S (NGC 3783 only).…”
Section: Abundances From Narrow Absorption Linessupporting
confidence: 76%
See 1 more Smart Citation
“…For the 40 ks RGS spectrum of NGC 3783, Blustin et al (2002) measured the abundances to be consistent with solar, with the exception of Fe. Similar abundances were measured by Steenbrugge et al (2003) for NGC 5548 using a 137 ks RGS spectrum, as well as by Blustin et al (2007) for a 160 ks RGS spectrum of NGC 7469. Holczer et al (2007) determined the abundances for IRAS 13349+2438 and NGC 3783 using the updated dielectronic recombination rates and determined abundances relative to Fe consistent with proto-solar ratios for O, Ne, Mg, Si, and S (NGC 3783 only).…”
Section: Abundances From Narrow Absorption Linessupporting
confidence: 76%
“…For instance, Schmidt et al (2006) and Nahar et al (2009) performed detailed atomic calculations of the di-electronic recombination rates. Schmidt et al (2004) measured the wavelengths of the O v lines, after Steenbrugge et al (2003) had noted that the wavelength used for the 22 Å line was likely to be wrong. In their Appendix 1, Detmers et al (2011) list the atomic data that has been updated prior to the analysis of the RGS and LETGS spectra of Mrk 509.…”
Section: Abundances From Narrow Absorption Linesmentioning
confidence: 99%
“…K-shell photoabsorption of oxygen and its ions is often responsible for prominent features in the interstellar medium (ISM) absorption spectra in the 500-600-eV photon energy range. Indeed oxygen K-shell absorption lines have been observed towards both low-mass x-ray binaries [1][2][3][4][5] and active nucleus of Seyfert galaxies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…From a dynamical modeling of the BLR (Pancoast et al 2014), it is inferred that this source is observed at an inclination angle of ∼30 • and hosts a supermassive black hole (SMBH) of ∼3 × 10 7 M in its center. Previously, high resolution UV (Crenshaw & Kraemer 1999;Crenshaw et al 2003a) and X-ray (Kaastra et al , 2002Steenbrugge et al 2003Steenbrugge et al , 2005) spectra have revealed several deep NAL that can be ascribed to a moderate velocity (v out = 200−1200 km s −1 ) ionized outflow.…”
Section: Introductionmentioning
confidence: 99%